GE_GERICHTE P/3884/2015 vom 1. Juli 2016 - GE Cour de justice (2016)
VOL(DROIT PÉNAL); ENTRÉE ILLÉGALE; APPAREIL DE PRISE DE VUE; SURVEILLANCE(EN GÉNÉRAL); APPRÉCIATION DES PREUVES | CP.139.1; CP.42.2; LEtr.115.1.a; CPP.10.2